The Role of Smart Agriculture in Promoting Sustainable Development - Successful International Experiences - Yacine, BOURAYOU Mohammed (Journal of Ecohumanism, 2024)
The present study aims to shed light on the role and contribution of smart agriculture in achieving sustainable development by addressing the importance of modern technology in the agricultural sector to enhance sustainable development. This is done through presenting successful international experiences that have adopted modern technology strategies to improve the agricultural sector and promote sustainable development. The study clarifies the concept of smart agriculture and its areas of application, as well as the resulting advantages for the agricultural sector in Arab, African, and Asian countries. It also explores the various policies adopted by Africa at both continental and regional levels to support the implementation of smart agriculture. Moreover, the study highlights the challenges facing this significant transformation in the African agricultural sector.